Implementation of the Principal's Strategy in Development Talents and Interests of Students (Multi-Site Study at MTsN 3 Nganjuk and MTsN 2 Kediri City) (International Journal of Education and Literature, 2022)
The research in this dissertation is motivated by the phenomenon of the development of quality educational institutions that have a good process to create high student achievement, design a good curriculum taught by qualified teachers and good products as evidenced by the students being able to compete with superior schools. inside and outside the city so that, with a good process, Madrasa are no longer underestimated and even become the community's main choice of superior schools. The research approach uses qualitative methods. Data collection techniques are participant observation, in-depth interviews and documentation. The data analysis techniques used are 1) single case data analysis, 2) cross-site analysis. From the results of this study, it can be concluded that: ( 1) The formulation of the madrasa principal's strategy in developing students' talents and interests at MTsN 3 Nganjuk and MTsN 2 Kediri City is carried out by : formulating the vision and mission of the madrasa, determining the goals of planning for the development of student talents and interests that have been carried out by the madrasa, mapping talents and interests based on abilities and fields of study . Recruitment of basic education students with implementation of strict selection assessment taking into account several assessments, namely the recruitment of the academic path through with report cards and Olympics. Non-academic selection recruitment is seen from the results of students' memorization of the Koran, sports, arts and so on . (2) The implementation of the madrasa principal's strategy in developing students' talents and interests at MTsN 3 Nganjuk and MTsN 2 Kediri City is carried out by: 1) Programs of extracurricular activities provided for all students according to their potential, interests, talents, and abilities, so that students can develop maximally. 2) Supporting activities through routine and spontaneous activities that are carried out optimally can develop students' talents and interests.